Factors Influencing Poverty in The Province of North Maluku - Askal Samiudin (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2023)
ABSTRACTThe purpose of this study is to identify the factors that affect the poverty level in North Maluku province. This study is a type of quantitative descriptive research that uses primary and secondary data. The method of data collection involves obtaining information from the official website of the Central Bureau of Statistics (PBS) and other sources that support this research. The results of hypothesis testing show that there is no relationship between the open unemployment rate (OUR) and poverty in North Maluku. Additionally, a negative relationship was found between literacy rate (LR) and poverty, which means that the lower the literacy rate, the higher the poverty level. Furthermore, the life expectancy variable (LE) was found to have an influence on the poverty level in North Maluku. for future researchers to be able to add variables and scope of data collection so that the research can be even better.Keywords: influence of OUR, LR, and LE on poverty.